A Simplified Technique for All-Inside Tibial Socket Retrograde Drill Guiding Using a 2- to 3.5-mm Concentric Cannula Without the All-Inside Tibial Guide Ring - Yizhong Peng, M.D., Ph.D.; Wenbo Yang, M.D., Ph.D.; Wei Yu, M.D., Ph.D.; Chunqing Meng, M.D., Ph.D.; Hong Wang, M.D., Ph.D.; Wei Huang, M.D., Ph.D. (Arthroscopy Techniques)
The all-inside anterior cruciate ligament (ACL) technique is a minimally invasive surgical procedure that has gained popularity due to its reduced invasiveness and improved patient outcomes. The establishment of tibial sockets remains a crucial step in ACL reconstruction, which has always been difficult in ACL reconstruction research. For doctors who are not very experienced, this technique of positioning and making sockets requires a special guide ring, and the tunnel entrance is prone to be anterior. Herein, we report a simplified technique using a self-made 2- to 3.5-mm concentric cannula to help surgeons easily master the all-inside technique. Our technique for tibial socket construction does not require the specific tibial guiding ring but uses a traditional tibial guiding ring for full-length tibial tunnel construction. With a 2-mm Kirschner wire and the traditional tibial guiding ring initially locating the tunnel position, the self-made concentric cannula helps combine the Kirschner wire with the guide pin sleeve, thereby impacting the guide pin sleeve into the tibial cortex at a controlled depth. Then, retrograde drilling is performed to create the socket. This technique provides feasible approaches for surgeons to transition from traditional full-long tunnel creation to the semi-long socket construction for the all-inside ACL technique.